Analysis Of Consumer Preferences Analysis Of Consumer Preferences In The Selection Of Cosmetic Mascara: Analysis Of Consumer Preferences In The Selection Of Cosmetic Mascara - Dela Pradana Sari (Universitas Negeri Jakarta, 2021)
Women define beauty as the condition of the skin on the body and face that looks clean and has curly eyelashes. The beauty of the eyes does not radiate perfectly without a hint of mascara. This study aims to determine and analyze the attributes of mascara products that are consumer preferences and the types of mascara attributes that most influence consumer preferences for purchasing decisions in the selection of mascara cosmetics on consumers at Kota Kasablanka Mall. The sample in this study was obtained using incidental sampling technique with the slovin formula. The analytical method used is a quantitative method with a descriptive approach. Determining mascara attributes to be consumer preferences using the Chi Square test and which is the main preference requires Fishbein's multi-attribute analysis test. Based on the results of Fishbein's multi-attribute analysis test on mascara attributes, it was found that the attitude value of respondents (Ao) was product quality 23.70, color 22.93, brand 20.50, price 18.00, and packaging 13.88. The higher the value (Ao), the mascara attribute is the first most considered by respondents. The preference that consumers consider the most in the selection of cosmetic mascara is the quality of the product. Based on the results of the Chi Square analysis test on mascara attributes, it was found that Asymp. Sig product quality 0.642 > 0.05, Asymp. Sig color 0.161 > 0.05, Asymp. Brand sig 0.31 > 0.05, Asymp. Sig price 0.001 < 0.05, and Asymp. Sig packing 0.002 < 0.05. Product quality, color and brand have significant values ​​because Ho is accepted and Ha is rejected. Mascara attributes that have an influence on respondents' preferences in choosing mascara cosmetics are product quality, color, and brand. Keywords: Mascara attributes, consumer preferences, product quality